Possibilities of Using Transplantation of Autologous Adipose Tissue Enriched with Stem Cells in Mammoplasty - Супхонов Умар Умедович; Абдурахмонов Дийор Шукуруллаевич (European Science Publishing, 2024)
Every year, the number of cases of mammoplasty performed for cosmetic indications increases. However, breast surgeries are often performed for more than just aesthetic reasons. The trend of increasing incidence of breast cancer in women continues [1–3]. Among the technologies of combined treatment of patients with breast cancer, the surgical method remains fundamental. At the same time, both radical mastectomy and partial resections gl.mammae after surgery, it is invariably accompanied by the formation of breast deformities. The latter causes a deterioration in the quality of life of women with breast cancer, reducing the possibilities of their speedy social adaptation [4].